Polymorphism of Pituitary-Specific Transcription Factor-1 (Pit-1) Gene at Locus (Pit-1-Hinf1) and its effects on dam body weight and milk production of local sheeps - Sumantri, C.; Herdiana, D.; Farajallah, A.; Rahmat, D. (Indonesian Animal Sciences Society, 2009)
Pituitary-Specific Transcription Factor-1 (Pit-1) is a transcription factor with critical role in the transcriptional regulation of multiple genes in the pituitary. The objective of this research was to identify polymorphism of Pituitary-Specific Transcription Factor-1 (Pit-1) gene at Locus (Pit-1-Hinf1) and to investigate any possible associations of Pit-1 genotypes on dam body weight, milk production and milk quality in local sheep at the Jonggol Animal Science Teaching and Research Unit (JASTRU), Fact. Anim. Sci. Bogor. Agric. Univ. A total number of 161 blood samples were collected from 3 local sheep, namely Garut from Wanaraja (55 hd), Garut from Margawati (23 hd) and lactating ewes (83 hd) from JASTRUÂ farm in Bogor. Genomic DNAs were extracted by a standard phenol-chloroform protocol and amplified by a polymerase chain reaction (PCR) techniques, then PCR products were digested with a Hinf1 enzyme restriction. Fragments of Pit-1gene at locus Pit-1-Hinf1 was detected by a silver-staining method. A length of 637 base pairs (bps) of the Pit-1 gene of local sheep was successfully amplified. The Hinf1 restriction enzyme cut the PCR product into three different length of fragments succesively at 345, 137, and 115Â Â bps designated as A allele; whilst B allele had four fragments at 283, 137, 115, and 62 bps respectively. The locus of Pit-1-Hinf1 was polymorphic in local sheep from Jonggol, however it was monomorfic in Garut sheep. The frequencies of A and B alleles were 0,806 and 0,194 respectively. Pit-1 genotypes had no significant effect on dam body weight and milk production. This result is indicating that the use of single locus Pit-1-Hinf1 in Pit-1 gen is less effective to be used as a candidate in selecting dam body weight and milk production in these three local sheep. Key words: Local Sheep, Pit-1 Gene, Polymorphism, Dam, Milk